ANALISIS PERAMALAN PERMINTAAN PRODUK WOODEN BOX DAN WOODEN PALLET DI PT XYZ - M, Pretty Agustin; Susanti, Elva (Computer Science and Industrial Engineering, 2020)
Forecasting is a prediction of a future that got from detailed calculation results systematically based on current data and previous data in the certain period. To do forecasting, a lot of data that used to do a forecasting then our result could be accurate based on forecasting that we have already done. Forecasting of demand is needed by PT XYZ, Forecasting method that used are Exponential Smoothing method with α 0,1, 0,5 and 0,9 and Regression Linier method to predict the number of sales product of wooden box and wooden pallet that would occur in the months to come. The forecasting result with regression linear for six period later sequentially are 274,12; 274,99; 275,85; 276,71; 277,57; and 278,44 with the error level are MAD = 34,74; MSE = 1.637,51 and MAPE = 14,17%. From data processing analysis that already done that the best selected method is exponential smoothing with α 0,9 to forecast demand product of wooden pallet 110 cm x 110 cm. With forecasting result in six period later sequentially are 347,9; 369,7; 391,4; 413,2; 434,9; dan 456,7 with the error level are MAD = 4,14; MSE = 22,63 and MAPE = 1,65%.